Citizenship by Investment in Turkey and the USA: A Comparative Analysis - Konukcu, Yasemin; Yantur, Pelin (International Journal of Economics and Financial Issues, 2025)
In this article, the practice of citizenship by investment is analyzed comparatively. In this context, the transformation of the concept of citizenship is evaluated in the context of political theory. Citizenship, which has its origins in the extension of aristocratic rights, basically comprises a number of rights and duties. Historically, in countries such as the United Kingdom and Scotland, before the introduction of universal citizenship, it was possible for wealthy people to gain privileges by selling titles of nobility. However, the modern state has shaped the concept of citizenship through affiliations, identities and values. Therefore, citizenship by investment is a controversial practice in terms of its causes and consequences. In this study, the practices of granting citizenship in the USA after 1990 and similar practices in Turkey after 2016 are used as examples. The concept of belonging and identity has been replaced by the principle of “economic benefit”.